Strategic management theory and universities: An overview of the Special Issue. (February 2018) - Siegel, Donald S.; Leih, Sohvi
There are few theoretical frameworks to address organizational challenges and strategies of research universities. We conjecture that strategic management theory provides an opportunity to examine those challenges, such as increased competition, tight budgetary constraints, and rising stakeholder expectations. More specifically, the dynamic capabilities framework has emerged as a useful tool for universities to better manage important issues such as commercializing their innovations, partnering with industry and promoting economic and social development in their regions. Our essay and the papers in this special issue address these issues.